Gender gaps in labor informality: The motherhood effect - Inés Berniell; Lucila Berniell; Dolores de la Mata; María Edo; Mariana Marchionni (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2019)
Recent work has quantified the large negative effects of motherhood on female labor market outcomes in Europe and the US. But these results may not apply to developing countries, where labor markets work differently and informality is widespread. In less developed countries, informal jobs, which typically include microenterprises and self-employment, offer more time flexibility but poorer social protection and lower labor earnings. These characteristics affect the availability of key inputs in the technology to raise children, and therefore may affect the interplay between parenthood and labor market outcomes. Through an event-study approach we estimate short and long-run labor market impacts of children in Chile, an OECD developing country with a relatively large informal sector. We find that the birth of the first child has strong and long lasting effects on labor market outcomes of Chilean mothers, while fathers remain unaffected. Becoming a mother implies a sharp decline in mothers' labor supply, both in the extensive and intensive margins, and in hourly wages. We also show that motherhood affects the occupational structure of employed mothers, as the share of jobs in the informal sector increases remarkably. In order to quantify what the motherhood effect would have been in the absence of an informal labor market, we build a quantitative model economy, that includes an informal sector which offers more flexible working hours at the expense of lower wages and weaker social protection, and a technology to produce child quality that combines time, material resources and the quality of social protection services. We perform a counterfactual experiment that indicates that the existence of the informal sector in Chile helps to reduce the drop in LFP after motherhood in about 35%. We conclude that mothers find in the informal sector the flexibility to cope with both family and labor responsibilities, although at the cost of resigning contributory social protection and reducing their labor market prospects.
Keywords: J13; J16; J46; 330; gender pay gap; child penalty; developing countries; labor informality; Chile